Perbandingan Tingkat Sedasi Klonidin Syrup 2 mcg/kgBB dengan Diazepam Syrup 0.4 mg/kgBB sebagai Premedikasi pada Pasien Anak yang Menjalani Pembedahan dengan General Anestesi - Vera Muharrami; A. Sani P. Nasution; Nazaruddin Umar (Fakultas Kedokteran Universitas Riau, 2011)
Introduction: Anxiety in children undergoing surgery is characterized by subjective feeling of tension, apprehension,nervousness and worry that may be expressed in various forms. Clonidine, an alpha 2-adrenoceptor agonist, has beenshown to be as a preanesthetic medication in childrens. The current study was designed to investigate the differencesof level sedation clonidine syrup and diazepam syrup as a premedicant in children.Methods: In a randomized, double-blind, controlled clinical trial, 40 children, aged 2-12 yr, undergoing electivesurgery received 2 micrograms/kg clonidine syrup or 0.4 mg/kg diazepam syrup orally. These agents were administered120 min before the estimated time of induction of general anesthesia and noted the children’s level of sedation. Thelevel of sedation were compared among the two groups. PASS <1 demanded rescue intravenous sedation.Result: Clonidine syrup 2 mcg/kgBB provided better quality of sedation after 60 min of premedicant but it wasn’tsignificant(1.8±0.92) and diazepam syrup (0.80±0.89; p>0.05) and number of patients with rescue intravenous diazepamacceptance were same both clonidine group compared to diazepam, there was no significant difference between twogroups, 10% of clonidine group patients, 10 % of diazepam group patients (p>0.05). No clinically significanthypotension or bradycardia was observed after preanesthetic medications of diazepam and clonidine syrup.Discussion: These data indicate that, even in pediatric surgery, the 2 micrograms/kg syrup clonidine is an effectivepremedication. However, the safety and optimal dose of clonidine in this setting remain to be determined.